An Integrative Literature Review of Organisational Factors Associated with Admission and Discharge Delays in Critical Care. (19th October 2015) - Peltonen, Laura-Maria; McCallum, Louise; Siirala, Eriikka; Haataja, Marjaana; Lundgrén-Laine, Heljä; Salanterä, Sanna; Lin, Frances
Abstract : The literature shows that delayed admission to the intensive care unit (ICU) and discharge delays from the ICU are associated with increased adverse events and higher costs. Identifying factors related to delays will provide information to practice improvements, which contribute to better patient outcomes. The aim of this integrative review was to explore the incidence of patients' admission and discharge delays in critical care and to identify organisational factors associated with these delays. Seven studies were included. The major findings are as follows: (1) explanatory research about discharge delays is scarce and one study on admission delays was found, (2) delays are a common problem mostly due to organisational factors, occurring in 38% of admissions and 22–67% of discharges, and (3) redesigning care processes by improving information management and coordination between units and interdisciplinary teams could reduce discharge delays. In conclusion, patient outcomes can be improved through efficient and safe care processes. More exploratory research is needed to identify factors that contribute to admission and discharge delays to provide evidence for clinical practice improvements. Shortening delays requires an interdisciplinary and multifaceted approach to the whole patient flow process. Conclusions should be made with caution due to the limited number of articles included in this review.